2021
DOI: 10.3390/md19040192
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Volatile Composition of Seven Seaweeds from the Yellow Sea of China

Abstract: Plant volatile organic compounds (VOCs) represent a relatively wide class of secondary metabolites. The VOC profiles of seven seaweeds (Grateloupia filicina, Polysiphonia senticulosa, Callithamnion corymbosum, Sargassum thunbergii, Dictyota dichotoma, Enteromorpha prolifera and Ulva lactuca) from the Yellow Sea of China were investigated using multifiber headspace solid phase microextraction coupled with gas chromatography–mass spectrometry (HS-SPME/GC–MS), among them, the VOCs of three red algae Grateloupia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…These two compounds were not present in our previous research of fresh D. dichotoma headspace [14], but the sample was from a different singlepoint collection location. On the other hand, pentadecane was found in the headspace of D. dichotoma from the Yellow Sea of China [15]. Another present higher alkane was heptadecane (up to 3.53% (I) or 2.35% (II)), which was not present in the research of Wang et al [15].…”
Section: Variations Of Headspace Volatilome Of Fresh D Dichotomamentioning
confidence: 79%
See 1 more Smart Citation
“…These two compounds were not present in our previous research of fresh D. dichotoma headspace [14], but the sample was from a different singlepoint collection location. On the other hand, pentadecane was found in the headspace of D. dichotoma from the Yellow Sea of China [15]. Another present higher alkane was heptadecane (up to 3.53% (I) or 2.35% (II)), which was not present in the research of Wang et al [15].…”
Section: Variations Of Headspace Volatilome Of Fresh D Dichotomamentioning
confidence: 79%
“…In our previous research [14], sesquiterpenes were found among D. dichotoma headspace VOCs, predominantly germacrene D followed by other cadinenyl (abundant), muurolenyl and amorphenyl structures. The headspace VOCs in D. dichotoma from the Yellow Sea of China were also characterised as sesquiterpenes (predominantly germacrene D) and diterpenes [15]. However, there is a gap in the research on less volatile compounds of D. dichotoma as well as about VOC seasonal variability that could be also important for the algal chemotaxonomy or biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aldehydes are representative of the so-called “green odour” substances, which play an active role as repulsive and impressive in plant and insect interactions [33] . Wang et al [5] analysed the VOCs of three red seaweeds ( Grateloupia filicina , Polysiphonia senticulosa and Callithamnion corymbosum ) from the Yellow Sea of China and found that the main VOCs were aldehydes, ketones, alkenes and alcohols. As previous reported by Gressler et al [34] , algae-derived compounds, only 46 metabolites were identified as terpenes, alcohols, acids, esters, ketones, and hydrocarbons detected.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the seaweeds exhibit a large number of VOCs are released for a variety of reasons, including: increasing tolerance to abiotic stresses; communicating stress to homogeneous algae to induce defence; playing allelopathic roles on heterogeneous algae and aquatic macrophytes for competing nutrients; and protecting against predators. The majority of research on VOCs in macroalgae has concentrated on their allelopathy effects, whereas their contributions in other areas have received far less attention [5] . Additionally, polyphenols including one or more aromatic rings bearing hydroxyl groups are perhaps the category of phytochemicals substances in seaweed that have garnered the most interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the formation mechanisms of these volatile compounds, such as the presence of halogenated sesquiterpenes, diterpenes, and acetylenes in red algae, are still not fully understood [ 14 , 15 ]. Despite this, VOCs are still the main analytes responsible for the organoleptic profiles of seaweeds and deserve proper attention, not only due to this fact but also due to their potential hazardousness and toxicity for humans [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%